Crème de la Crème: The Teach For All Experience and Its Lessons for Policy-Making in Latin America - Belen Cumsille R.; Ariel Fiszbein (Arizona State University, 2015)
This paper analyzes the experience of Teach For All partners in different countries around the globe in three areas: (a) Recruitment and Selection; (b) Training and Development; and (c) Placement. Using information from semi-structured interviews with Teach For All staff members and national partners, we analyze the key elements of the Teach For All approach in these areas. Based on that analysis we argue that Teach For All's active recruitment and rigorous selection of candidates, emphasis of quality over length in training, the continued support offered to teachers and the heavy emphasis on data and evaluation constitute practices that, if pursued at the systems level, could enhance the quality of teaching and, consequently, learning outcomes in Latin America.